Evaluation of the freight Intelligent Transportation System (ITS) on transportation operations - Choo, Gim Hwee; Ismail, Mohd Azril (2012)
The purpose of this paper is to create a general overview on how the Intelligent Transportation System (ITS) supports freight transportation operations.This overview is established through studying various freight intelligent transportation systems, freight transportation information types, and transportation operations in terms of functions and performance dimensions.To prepare the paper, a literature study was made through secondary sources and methods.The finding of the study is nine freight ITS and different transportation information types that freight ITS work based on their availability are generated and recognized.The transportation functions and performance dimensions are improved after application of freight ITS.